Herpes Simplex Virus Reactivation After Hemispherectomy for Intractable Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at the Cleveland Clinic report a 23-month-old immunocompetent boy with reactivated herpes simplex virus encephalitis (HSE) after a subtotal hemispherectomy for seizures related to HSE-associated right middle cerebral artery infarction at 7 months of age.